Subtidal macrophyte diversity and potentials in Nha Trang Bay - baseline data for monitoring a rising natural resource. (30th September 2021) - Fricke, A.; Nguyen, X.V.; Stuhr, M.; Hoang, T.D.; Dao, V.H.; Tran, M.D.; Pham, T.S.; Le, H.C.; Le, M.H.; Pham, Q.L.; Schmid, M.; Kunzmann, A.; et al.
Abstract: Tropical coastal ecosystems provide a unique complex marine habitat with a high diversity of algal species, Viet Nam being a particular hotspot. These algae may host a variety of potential unknown or underestimated bioactive algal compounds. In parallel the worldwide rising interest in macroalgae-based products leads to increasing activities in seaweed natural harvest and mariculture within coastal waters. With this growing interest, the present work provides baseline data for a systematic and science-based macroalgal monitoring program in Nha Trang Bay, Viet Nam, to keep track of potentially interesting taxa and to identify driving environmental factors which may also naturally influence biodiversity and species abundance. The present study investigated macrophyte diversity and abundance by combining a qualitative and quantitative macroalgal survey approach with environmental sampling (e.g. physicochemical properties of water column, underwater light regime, and sediment characteristics). Surveys were performed in the dry season (May/June) 2019 in different water depths (3, 6 and 10 m) at seven sites within Nha Trang Bay. The study revealed a coastal patchwork of diverse habitats inhabited by complex macrophyte communities, including estuarine dense Sargassum forests and Turbinaria meadows, sheltered sandy seagrass ( Halodule spp.) beds with upcoming Lyngbya blooms, low diverse Padina deserts and highly turbid aquaculture (lobster and fish farms) impacted sites with surprisingly high macroalgal diversity. During our study a total of 86 macrophyte species were encountered in the subtidal (>1 m water depth), whereas only 6 species ( Padina australis, Sargassum mcclurei, Turbinaria ornata, Halimeda discoidea, Amphiroa fragilissima, Tricleocarpa cylindrical ) were frequently found at every survey site. The observed high patchiness and presence of economically important (e.g. Sargassum spp., Gracilaria spp., Caulerpa spp., Gelidiella acerosa, Acanthophora spicifera ) and potentially economically interesting (e.g. Padina australis, Turbinaria ornata, Stypopodium zonale, Chondria armata ) taxa during the survey underlines the high potential of the present macrophytic bio-resource, which apparently is strongly structured and will be altered by the changing heterogenic environment. Graphical abstract: Image 1 Highlights: High macrophyte diversity and patchiness: only 6 from 86 species at all sites. Padina australis was the most abundant species. Macrophytic differences within and between sites decreased with water depths. Photo quadrat method was generally equivalent to the more destructive biomass method. Water temperature and estuarine impact clearly structured macrophytic communities.